Reasons full-time students of economics in Poland undertake jobs - Ostoj, Izabela (Managerial Economics, 2019)
Observation of the behavior of full-time students at economics universities in Poland reveals that a signifi cant percentage of these students combine studying with gainful employment. In Summariesthe literature there is a lack of research results and theorization concerning the decision-making mechanisms of full-time students choosing to combine studying with work. The assumption proposed in the article is that an employment-seeking student may perceive work primarily as a source of income or, alternatively, he/she may wish to gain professional experience that would make it easier for him/her to enter the labour market in the future. This article aims to investigate the motivations behind the decision to seek employment taken by full-time stu-dents of Economics in Poland. In particular, it attempts to identify the reasons behind starting a job and the criteria that played the most important role upon accepting a job offer. Focus is placed on the comparison between fi nancial motivations and reasons relating to professional development. This article uses the results of a survey created and conducted by the author. The conclusions based on these results indicate that the main source of motivation for engaging in gainful employment was fi nancial in nature and the primary criterion for choosing a particular employer was the level of compensation.